Colombia : Review Under the Flexible Credit Line Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Colombia's Review Under the Flexible Credit Line (FCL). Colombia continues to have very strong economic fundamentals and institutional policy frameworks. The policy adjustment to permanently lower oil prices was timely and decisive. Tight monetary policy helped anchor inflation expectations in the face of large but temporary inflation shocks. The exchange rate continued to float. Fiscal policy tightened as prescribed by the fiscal rule, while protecting social and infrastructure spending. A structural tax reform, including a 3 percentage-point increase in the value-added tax, became effective in January 2017. The IMF staff recommends the completion of the review under the FCL arrangement for Colombia.